The maximization of Bamed Health Care social media marketing in the pandemic era - Prana, Shinta Ragil (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
The Covid-19 pandemic has changed interaction patterns in socializing. Health service business players must be adaptive in marketing. Social Media Marketing (SMM) is the primary effective solution to promote brands by getting great exposure with minimum costs. By maximizing one IMC element correctly, the existence of the brand and health service business will be maintained. This study aims to determine the strategy of maximizing SMM as a communication medium for health services carried out by BAMED Health Care (BHC). The method used in this research is qualitative descriptive with a case study approach to investigate the depth of steps BHC took during interaction with consumers through social media. The data collection techniques were observation through Instagram, online interviews, and literature studies. Based on the results, researchers analyzed the motivation of BHC in determining SMM strategy by maximizing SMM on their Instagram accounts. The researcher found that the motivation of BHC was to maximize SMM strategy for maintaining customer engagement during the Covid-19 pandemic by maximizing the creation of interesting educational content which was informative and persuasive, activating the Instagram Live feature to provide health education, and making online consultation hashtags. As an evaluation, BHC needs to have a dedicated department to manage SMM activities so that every activity is informed quickly on social media, activates hashtags by making activities such as giveaways, and adds Instagram Live activities carried out on an ongoing basis to achieve even better success.